Go Hence; Have More Talk of These Sad Things: Reading and Relationality in the English Language Arts Classroom - Schaufele, Morgan (Journal of the Canadian Association for Curriculum Studies, 2020)
Drawing upon my own experiences as a high school English Language Arts teacher, I seek a satisfying response to offer students when they ask, “Why are we reading this?” Such a query often leads teachers and students to consider broader questions of the purposes of literature. This paper presents a hermeneutic exploration of the practice of teaching (with) literature in the high school classroom. Using the writings of Gadamer (1989/2013) and Sumara (1996, 2002), and their conceptualizations of aesthetic (literary) experience, I outline a process of engaging with students in their desire to understand their roles as readers in the classroom. In doing so, I make an argument for playful and dialogic interactions between reader and text—an approach that both retains the integrity of aesthetic experience, and also invites a relational pedagogy among those who share a literary reading.